2010
DOI: 10.1016/j.ijsolstr.2009.11.017
|View full text |Cite
|
Sign up to set email alerts
|

On the most dangerous V-notch

Abstract: a b s t r a c tThe determination of the failure load for brittle or quasi-brittle specimens containing a re-entrant corner has been faced by several authors, whose approaches are available in the Scientific Literature. However, up to now, little attention has been paid to the presence of a minimum, i.e. an angle at which the critical load attains its minimum value. Even if the minimum was detected in several experiments, it was not highlighted or it was considered as a mere consequence of the scattering of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…More recent is the discussion on the effect of the second order terms, which play a role analogous to that shown by T-stress in the crack case (Ayatollahi and Aliha 2009;Ayatollahi and Dehghany 2010;Ayatollahi and Nejati 2011), as well as on the conditions characterizing the most dangerous V-notch (Carpinteri et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…More recent is the discussion on the effect of the second order terms, which play a role analogous to that shown by T-stress in the crack case (Ayatollahi and Aliha 2009;Ayatollahi and Dehghany 2010;Ayatollahi and Nejati 2011), as well as on the conditions characterizing the most dangerous V-notch (Carpinteri et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental results [1][2][3][4] concerning three-point bending (TPB) and tensile tests on Vnotched brittle or quasi-brittle material specimens, show that the failure load does not increase monotonically as the notch opening angle 蠅 increases, but it has a minimum in correspondence of a critical angle 蠅 c . The problem of determining 蠅 c was investigated in [5] to what concerns a semi-infinite edge V-notched slab and it is here extended to a center Vnotched infinite slab under remote tensile load, when the notch is subjected to mode I loading. Four different criteria based on a discrete crack advancement [2,[6][7][8] are taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Carpinteri et al [37] showed that in sharp V-notches, an angle exists providing a minimum failure load. On the other hand, it has been found in this paper that, in U-notches, where the notch angle is zero and the singularity does not exist on the notch tip, a notch root radius different from zero exists, providing a minimum failure load.…”
Section: Introductionmentioning
confidence: 99%